Analisis Kebijakan Dividen dan Kebijakan Leverage terhadap Prediksi Kepemilikan Manajerial dengan Teknik Analisis Multinomial Logit - Luciana Spica Almilia; Meliza Silvi (Jurnal Akuntansi dan Bisnis, 2006)
This research has a purpose to provide empirical evident about factors that affect probability of managers to engage in managerial ownership. The examined factors on this research are leverage policy, dividend policy, size, investment opportunity, profitability, tobins q, and equity market value. The samples consist of 337 firms which had not managerial ownership, 87 firms had 0,1% -14,61% managerial ownership, and 42 firms which had 16,61% - 76,50% managerial ownership. Moreover, it is chosen by purposive sampling. The statistic method used to test on the research hypothesis is multinomial logit regression. The result shows that leverage policy, investment opportunity, profitability, tobins q, and equity market value are significant variables in determination managerial ownership. This research also indicates that investment opportunity and equity market value are significant variables in determination firms which had small and large managerial ownership.